2006
DOI: 10.1007/s00421-006-0135-7
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal responses to opioid receptor blockade: during rest and exercise in cold and hot environments

Abstract: Opioid receptors appear to modulate a variety of physiological and metabolic homeostatic responses to stressors such as exercise and thermally extreme environments. To more accurately determine the role of the naloxone (NAL) sensitive opioid receptor system during rest and exercise, subjects were subjected to concomitant environmental thermal stress. Fifteen untrained men rested or performed low intensity (60% VO2peak) or high intensity (80% VO2peak) exercise on a cycle ergometer for 60 min in an environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Previous studies showed that exposure to cold air attenuated the increase in ACTH and b-endorphine concentrations in response to high-intensity exercise and drug administration [6]. These findings suggest that ACTH can be used as a marker of fatal hypothermia.…”
Section: Introductionmentioning
confidence: 68%
“…Previous studies showed that exposure to cold air attenuated the increase in ACTH and b-endorphine concentrations in response to high-intensity exercise and drug administration [6]. These findings suggest that ACTH can be used as a marker of fatal hypothermia.…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, the opioid receptor system seems to regulate the physiological responses to exercise in thermally stressful environments 27. Nevertheless, responses of GH, cortisol and testosterone to these contradicting stresses is unknown and presents a unique summated stress to the athlete.…”
mentioning
confidence: 99%
“…However, the inhibition of beta-adrenoceptors did not affect the cortisol response to stress of 5-min exercise in pigs ( Weiss et al, 1974 ). Different stressors activate the hypothalamic-pituitary-adrenal axis together with increased endogenous opioid activity ( Akil et al, 1984 ;Der-Avakian et al, 2005 ;Armstrong, 2006 ;Rushen et al, 1993 ). Naloxone increased ACTH and cortisol in resting as well as restrained gilts ( Janssens et al, 1995 ;Rushen et al, 1993 ).…”
Section: Introductionmentioning
confidence: 95%